Physical Activity and Bone Vascularization: A Way to Explore in Bone Repair Context? - Rkia Wazzani; Stéphane Pallu; Céline Bourzac; Saïd Ahmaïdi; Hugues Portier; Christelle Jaffré (Life, 2021)
Physical activity is widely recognized as a biotherapy by WHO in the fight and prevention of bone diseases such as osteoporosis. It reduces the risk of disabling fractures associated with many comorbidities, and whose repair is a major public health and economic issue. Bone tissue is a dynamic supportive tissue that reshapes itself according to the mechanical stresses to which it is exposed. Physical exercise is recognized as a key factor for bone health. However, the effects of exercise on bone quality depend on exercise protocols, duration, intensity, and frequency. Today, the effects of different exercise modalities on capillary bone vascularization, bone blood flow, and bone angiogenesis remain poorly understood and unclear. As vascularization is an integral part of bone repair process, the analysis of the preventive and/or curative effects of physical exercise is currently very undeveloped. Angiogenesis–osteogenesis coupling may constitute a new way for understanding the role of physical activity, especially in fracturing or in the integration of bone biomaterials. Thus, this review aimed to clarify the link between physical activities, vascularization, and bone repair.